2018
DOI: 10.5888/pcd15.170570
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of High Blood Pressure by Nativity Among Black Men: Implications for Interpreting the Immigrant Health Paradox

Abstract: IntroductionDifferences in the social determinants of health and cardiovascular health outcomes by nativity have implications for understanding the immigrant health paradox among black immigrants. We aimed to understand whether blood pressure awareness, a precursor to achieving blood pressure control among hypertensive patients, varied by nativity among a sample of black men.MethodsData were collected from 2010 through 2014. In 2016, we conducted logistic regression models using data from a large sample of urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, due to the rising burden of non-communicable diseases (NCDs) and as more immigrants become long-term residents in the U.S., the prevention and management of chronic health conditions has become increasingly important [7]. Recent research has revealed high prevalence but low awareness of cardiometabolic disease among African immigrants in the U.S. [8,9]. Other studies of African immigrants living in high-income settings have found low levels of health insurance [10] and linkage to primary care [11,12] as well as low or delayed uptake of vaccination [13,14], cancer screening [15,16], antenatal care [17], and diabetes screening [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the rising burden of non-communicable diseases (NCDs) and as more immigrants become long-term residents in the U.S., the prevention and management of chronic health conditions has become increasingly important [7]. Recent research has revealed high prevalence but low awareness of cardiometabolic disease among African immigrants in the U.S. [8,9]. Other studies of African immigrants living in high-income settings have found low levels of health insurance [10] and linkage to primary care [11,12] as well as low or delayed uptake of vaccination [13,14], cancer screening [15,16], antenatal care [17], and diabetes screening [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, foreign-born blacks have been found to have lower rates of cardiovascular diseases including heart disease and obesity, than US-born blacks (47). To understand the role of the immigrant health paradox in health disparities among black US immigrants, focus on the differences in health outcomes by nativity is required (48). Also, there exists a strong distrust of the experiences (51).…”
Section: Discussion 16mentioning
confidence: 99%
“…While some differences within ethnic categories have been attributed to country of origin [4][5][6], others are related to differences in lived experiences in the US which result from differential experiences with discrimination and stigma [7][8][9]. Research into health differences within ethnic categories has also led to observations about immigration related health patterns, like the healthy immigrant paradox, which does not seem to hold for all ethnic groups [10][11][12][13][14]. While the majority of research in this area has focused on racial and ethnic minority groups, recent evidence suggests there is substantial diversity within the non-Hispanic White category on health measures found in the American Community Survey, which includes MENA Americans [15].…”
Section: Introductionmentioning
confidence: 99%